2004
DOI: 10.1227/01.neu.0000114141.37640.37
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Different Types of Resection for Pediatric Patients with Temporal Lobe Epilepsy

Abstract: Surgery for the treatment of juvenile TLE is successful and safe, but the resection type may influence outcomes. Results after AHs were disappointing, probably because of difficulties in precise localization of the epileptogenic focus among children. Neuropsychological results demonstrated minimal rates of deterioration and significant improvements in contralateral functions. Surgical treatment of juvenile TLE should be encouraged, but the use of especially left AH should possibly be restricted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1
3

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 42 publications
4
106
1
3
Order By: Relevance
“…5,6,18,19,23,26,29,30,34,36,37 In pediatric cohorts, 0%-14.6% major and 5.2%-19% minor complications are presented for various kinds of procedures. 3,4,7,20,33 In a systematic review of 76 studies in which different methodologies were used, Hader et † This includes 1 patient with thalamic infarction due to perforating artery injury, 1 patient with air embolism, and 1 patient with permanent postoperative anosmia. ‡ One patient had both a hemiparesis and a cranial nerve paresis, 1 patient a cerebral abscess and a persistent hemiparesis, 1 patient a postoperative hematoma and a persistent hemiparesis, 1 patient a persistent hemianopia and a persistent sensory deficit, and 1 patient a postoperative hematoma and a persistent hemianopia.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,18,19,23,26,29,30,34,36,37 In pediatric cohorts, 0%-14.6% major and 5.2%-19% minor complications are presented for various kinds of procedures. 3,4,7,20,33 In a systematic review of 76 studies in which different methodologies were used, Hader et † This includes 1 patient with thalamic infarction due to perforating artery injury, 1 patient with air embolism, and 1 patient with permanent postoperative anosmia. ‡ One patient had both a hemiparesis and a cranial nerve paresis, 1 patient a cerebral abscess and a persistent hemiparesis, 1 patient a postoperative hematoma and a persistent hemiparesis, 1 patient a persistent hemianopia and a persistent sensory deficit, and 1 patient a postoperative hematoma and a persistent hemianopia.…”
Section: Discussionmentioning
confidence: 99%
“…Selective amygdalohippocampectomy (SelAH), a procedure developed by Niemeyer in 1958, 25 produces postoperative seizure outcomes that are comparable to those attained after ATL. 26,39 Moreover, some studies have indicated that SelAH has better neuropsychological outcomes 6,14 and a lower risk of visual field defects 22 than ATL. On the other hand, some investigators have recorded neocortical epileptiform spikes with cortical electrodes, 1,35 indicating that tailored resection of the temporal neocortex is Selective amygdalohippocampectomy versus anterior temporal lobectomy in the management of mesial temporal lobe epilepsy: a meta-analysis of comparative studies essential for MTLE.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…Similar results were reported in a study on TLE patients; only 1 patient had poor seizure outcome of 27 patients with a lateral temporal lobe tumor who received lesionectomy (13 patients) or ATL (14 patients), whereas 2 of 7 patients who received lateral tumor resection with amygdalohippocampectomy had poor outcomes. 20 Tumors in the posterior temporal lobe can be regarded as extratemporal tumors in many aspects. In the current study, seizure outcome was mainly affected by the completeness of tumor removal; therefore, a lesionectomy could be a safe and effective procedure for these tumors.…”
Section: Surgical Strategymentioning
confidence: 99%